Employee job satisfaction of IDLC Finance Limited: a study on Gulshan Branch - Zaman, Raisa Tasneem (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.